2023
DOI: 10.1001/jamanetworkopen.2023.17164
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing vs Sliding Hip Screw in Trochanteric Fracture Management

Abstract: ImportanceFractures of the hip have devastating effects on function and quality of life. Intramedullary nails (IMN) are the dominant implant choice for the treatment of trochanteric fractures of the hip. Higher costs of IMNs and inconclusive benefit in comparison with sliding hip screws (SHSs) convey the need for definitive evidence.ObjectiveTo compare 1-year outcomes of patients with trochanteric fractures treated with the IMN vs an SHS.Design, Setting, and ParticipantsThis randomized clinical trial was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…7 However, two large randomized clinical trials have reported no difference in mortality at one year postoperatively. 6,9 On the other hand, higher 30-day mortality associated with IMN compared to SHS has been reported in two earlier large observational studies. 10,11…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…7 However, two large randomized clinical trials have reported no difference in mortality at one year postoperatively. 6,9 On the other hand, higher 30-day mortality associated with IMN compared to SHS has been reported in two earlier large observational studies. 10,11…”
Section: Introductionmentioning
confidence: 86%
“…1 While most guidelines recommend the use of IMNs for unstable trochanteric fractures (AO/OTA 31A3) 2 and subtrochanteric fractures, 3-5 there is growing evidence that SHSs and IMNs provide similar outcomes for stable trochanteric fractures (AO/OTA 31A1 and 31A2). 6,7 There is, however, an increasing trend internationally to use IMNs also for A1 and A2 fractures. 1,3,4,8…”
Section: Introductionmentioning
confidence: 99%
“…Authors from London (Canada) asked the question: Could the increased implant cost be justified by significantly superior outcomes of IMN fixation over SHS fixation? 1 A multinational team from the INSITE investigators set out to answer this question using a randomized controlled trial design. Their study was undertaken at 25 sites across 12 countries.…”
Section: Intramedullary Nailing Versus Sliding Hip Screw In Trochante...mentioning
confidence: 99%
“…The systematic review and meta-analysis, led by researchers from Boston (Massachusetts, USA), aimed to fill this gap by evaluating existing studies and collating robust evidence on this issue. 1 The study followed the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was registered in PROSPERO (ID: 380459). Searches were carried out in the studies with the I2 statistic.…”
Section: Oncologymentioning
confidence: 99%
“…We participated in a multicentric randomised controlled study (Identi cation No. : DRKS00003342) [30] to establish whether the Gamma3 nailing system has a positive impact on the quality of life of the patients compared with a SHS. We evaluated the EQ-5D Index and Visual Analogue Scale (VAS) scores, the Parker Mobility Score, the Harris Hip Score, the mortality rate and the change in the living situation and the use of walking aids 1 year after surgery.…”
Section: Introductionmentioning
confidence: 99%